LANGUAGE LEARNING METHODS AND STRATEGIES IN IMPOROVING STUDENTS’ LANGUAGE COMPETENCE IN THE ERA OF GLOBALISATION - Aslan Aslan; Muhammad Ishom (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study examines various effective language learning methods and strategies for improving students' language skills in the era of globalisation. Using a literature review method, this study examines the latest literature on language learning approaches that are adaptive to technological developments, cross-cultural communication needs, and diverse student characteristics. The results of the study show that communicative, task-based, collaborative learning methods and the use of digital technology are key to developing balanced and applicable language skills. In addition, learning strategies that emphasise active interaction, the use of authentic media, and constructive feedback play a significant role in stimulating motivation and the quality of language learning. This study provides recommendations for education practitioners to apply innovative and contextual methods and strategies in language learning so that students are able to compete and communicate effectively in an increasingly complex global world.